Pages of the past : exploring U.S. history through children's literature - Findlay, Diane, 1952- (Fort Atkinson, Wis : Upstart Books, 2002)
Presents discussion starters, annotated bibliographies, activities, and reproducible work sheets for grades 4-8 on American history, including the Revolutionary War, westward expansion, the Civil War, World War II, and other related topics.
"Grade level: 4-8"--Cover p. [4].
"Reading activities"--Cover.
Includes bibliographical references.
Professional
Keywords: Children's literature -- Study and teaching; Creative activities and seat work; Reading; Teaching -- Aids and devices; Children's literature -- Study and teaching; Creative activities; Reading; Teaching -- Aids and devices; United States -- History -- Study and teaching; United States -- History -- Study and teaching